Proces budżetowania w przedsiębiorstwie produkcji pasz - Sobów, Elżbieta (The Process of Budgeting in a Fodder-Making Company, 2006)
Budgeting in a company is a formal process, which is governed by specific principles of the creation and execution of a budget. The main purpose of a budget is short-term planning in such a way that during the budget period and during budgetary control we can define the sources of the deviations from the plan. We must remember, that we plan to rationalize and control costs. This is why the budget is a very important element of managing any business activity as it gives us the possibility to better evaluate the situation and make good decisions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 389-397